(untitled) (REMUNOM, 2024)
This research addresses the role of cooperativism in the context of the 2030 Agenda for Sustainable Development, adopted by the United Nations in 2015. The aim of the article is to investigate the contribution of cooperatives in addressing urban environmental challenges and their relevance in achieving the Sustainable Development Goals (SDGs). The adopted methodology is qualitative, exploratory, and descriptive, aiming to identify trends, challenges, and opportunities related to the integration of these concepts. The data analysis will be conducted qualitatively to provide a comprehensive view of the impacts of cooperativism on the adoption of SDGs. Through case studies and research, the article highlights how cooperatives contribute to specific goals of the 2030 Agenda, such as the eradication of poverty (SDG 1) and zero hunger (SDG 2). The conclusion emphasizes the adaptability and evolution of cooperatives, emphasizing their vital role in building a more sustainable and equitable world by the year 2030.